Determinants Of Decisions To Use Islamic Bank Mobile Banking Services - Saleh, Idris; Kadariah, Siti; Dewi, Indah Purnama (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The facts in the field, there are a number of customers who do not use Mobile Banking services, the problem is that banks have provided services but customers do not use Mobile Banking services and prefer manual transactions. This study aims to determine the effect of perceived ease of use, knowledge, and trust on the decision to use Islamic bank Mobile Banking services. The research discussion relates to banking services, namely services that discuss ease of use, knowledge, trust and decisions to use Islamic bank Mobile Banking services. This research is a quantitative research with multiple linear regression analysis, the data source used is primary data through questionnaires. The population of this study was the Padangsidimpuan community, the sample in this study used an accidental sampling technique, with 98 respondents. knowledge and trust have an influence on decisions to use Mobile Banking services. And simultaneously (F test) ease of use, trust and knowledge have a significant influence on the decision to use Mobile Banking services.Keywords: Determinant, Decision, Mobile Banking Service